Cardiac Surgery 2021 Reviewed - Doenst, Torsten; Schneider, Ulrich; Can, Tolga; Caldonazo, Tulio; Diab, Mahmoud; Siemeni, Thierry; Färber, Gloria; Kirov, Hristo (The Thoracic and Cardiovascular Surgeon, 2022)
PubMed displayed more than 35,000 hits for the search term “cardiac surgery AND 2021.” We used the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) approach and selected relevant publications for a results-oriented summary. As in recent years, we reviewed the fields of coronary and conventional valve surgery and their overlap with their interventional alternatives. COVID reduced cardiac surgical activity around the world. In the coronary field, the FAME 3 trial dominated publications by practically repeating SYNTAX, but with modern stents and fractional flow reserve (FFR)-guided percutaneous coronary interventions (PCIs). PCI was again unable to achieve non-inferiority compared with coronary artery bypass graft surgery (CABG) in patients with triple-vessel disease. Survival advantages of CABG over PCI could be linked to a reduction in myocardial infarctions and current terminology was criticized because the term “myocardial revascularization” is not precise and does not reflect the infarct-preventing collateralization effect of CABG. In structural heart disease, new guidelines were published, providing upgrades of interventional treatments of both aortic and mitral valve disease. While for aortic stenosis, transcatheter aortic valve implantation (TAVI) received a primary recommendation in older and high-risk patients; recommendations for transcatheter mitral edge-to-edge treatment were upgraded for patients considered inappropriate for surgery. For heart team discussions it is important to know that classic aortic valve replacement currently provides strong signals (from registry and randomized evidence) for a survival advantage over TAVI after 5 years. This article summarizes publications perceived as important by us. It can neither be complete nor free of individual interpretation, but provides up-to-date information for decision-making and patient information.
Keywords: coronary artery bypass grafts surgeryCABG; aortic valve replacement; mitral valve surgery; tricuspid valve